Pendapatan Usahatani Kelapa Di Desa Maliambao Kecamatan Likupang Barat Kabupaten Minahasa Utara - Iroth, Aprilia; Manginsela, Elsje Pauline; Lumingkewas, Jelly Ribka Danaly (Sam Ratulangi University, 2023)
The purpose of this study was to find out and describe the income of coconut farming farmers in Maliambao Village, west Likupang District, North Minahasa Regency. The data used in this study are primary data and secondary data. Primary data is obtained directly from respondents through interviews with structured questionnaires and observations. Data analysis method using income analysis.The results of this research show that the average income of coconut farmers in Maliambao District of Likupang Barata district of Minahasa North for a single harvest was IDR6.002.727,2 which was obtained from the difference between the average receipts of IDR7.798.000 minus the cost of IDR1.795.272,8.